KETIMPANGAN PENDAPATAN PROVINSI DI INDONESIA 2012-2016 - ANNISA FITRI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The object of this research is to analyze the inequality of income between provincestinIndonesiarwithbpanel1data1ingthesperiodr2012-2016. This study uses data from 34 Provinces and uses 2 conceptual frameworks with 3 test panel data models in selecting the best model. According to the test results show that the best model is the Common Effect Model (CEM) used inTanalyzing the factors affecting income inequality.The results showed that the variable of GRDP per capita (X1) had a negative and significant effect, the variable of population (X2) had positive effect but not significant and the variable (X3) Total (Capital Expenditure, Expenditure of Goods & Services and Employee Expenditure) had positive and significant effect on the Income Inequality in Province Indonesia in 2012-2016.        Keywords: Inequality Of Incomes, PDRB percapita, Net of people, Capital Expenditure, Goods & Services Expense, Employee Expenditure, Panel Data.